Synchrotron X‐ray microbeam dosimetry with a 20 micrometre resolution scintillator fibre‐optic dosimeter. (24th April 2018) - Archer, James; Li, Enbang; Petasecca, Marco; Stevenson, Andrew; Livingstone, Jayde; Dipuglia, Andrew; Davis, Jeremy; Rosenfeld, Anatoly; Lerch, Michael
Abstract : A scintillator fibre optic dosimeter with a one‐dimensional spatial resolution of 20 µm has demonstrated the ability to resolve synchrotron X‐ray microbeams. Abstract : Cancer is one of the leading causes of death worldwide. External beam radiation therapy is one of the most important modalities for the treatment of cancers. Synchrotron microbeam radiation therapy (MRT) is a novel pre‐clinical therapy that uses highly spatially fractionated X‐ray beams to target tumours, allowing doses much higher than conventional radiotherapies to be delivered. A dosimeter with a high spatial resolution is required to provide the appropriate quality assurance for MRT. This work presents a plastic scintillator fibre optic dosimeter with a one‐dimensional spatial resolution of 20 µm, an improvement on the dosimeter with a resolution of 50 µm that was demonstrated in previous work. The ability of this probe to resolve microbeams of width 50 µm has been demonstrated. The major limitations of this method were identified, most notably the low‐light signal resulting from the small sensitive volume, which made valley dose measurements very challenging. A titanium‐based reflective paint was used as a coating on the probe to improve the light collection, but a possible effect of the high‐ Z material on the probes water‐equivalence has been identified. The effect of the reflective paint was a 28.5 ± 4.6% increase in the total light collected; it did not affect the shape of the depth‐dose profile, nor did it explain an over‐response observed when used to probe at low depths, when compared with an ionization chamber. With improvements to the data acquisition, this probe design has the potential to provide a water‐equivalent, inexpensive dosimetry tool for MRT.